Observational and Comparative Study of Utility of Transabdominal Ultrasound in Diagnosis of Mild Acute Gastritis (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: acute gastritis; gastric erosion; mucosal erosions; mucosal thickness; layers; gut signature; sonography; ultrasound; gastric wall; stomach